PROFITABILITAS PADA EARNINGS RESPONSE COEFFICIENT DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI - Sintya Aryanti, Gusti Ayu Putu; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of profitability on earnings response coefficient by adding disclosure of corporate social responsibility as a moderating variable. This research is conducted in mining companies listed on the Indonesia Stock Exchange in 2012-2014. The number of samples taken are18 companies to obtain 54 observations for 3 years with purposive sampling method. Data are collected using the method of documentation. The analysis technique used is moderated regression analysis. The results show that profitability have a positive effect on earnings response coefficient. However, the disclosure of corporate social responsibility is not able to moderate the effect of profitability on earnings response coefficient. These results indicate that investorson mining companies in making investment decisions tend to attention profitability more than the disclosure of Corporate Social Responsibility.
Keywords: Profitability, Disclosure of Corporate Social Responsibility, Earnings Response Coefficient